Modulation of Epithelial Mesenchymal Transition after AGTR-1 Gene Edition by Crispr/Cas9 and Losartan Treatment in Mammary Tumor Cell Line: A Comparative Study between Human and Canine Species - Moschetta-Pinheiro, Marina Gobbe; Colombo, Jucimara; de Godoy, Bianca Lara Venâncio; Balan, Julia Ferreira; Nascimento, Bianca Carlos; Zuccari, Debora Aparecida Pires de Campos [UNESP] (MDPI, 2021)
Breast cancer is the most prevalent tumor type among women and female dogs. Tumor malignancy is characterized by the epithelial-to-mesenchymal transition (EMT) which leads to the metastasis formation. The inhibition of angiotensin II type I receptor (AGTR1) by an antagonist such as losartan can suppress angiogenesis, consequently contributing to the metastasis control. The aim of this study was to analyze the capacity of losartan and AGTR-1 gene edition to modulate the EMT process in triple negative/metastatic mammary tumor cells, compared to existing treatment protocols such as carboplatin. The cell lines CF41.Mg and MDA-MB-468, were cultured and treated with carboplatin, losartan, or submitted to AGTR-1 gene edition by CRISPR/Cas9. EMT markers and PARP-1 protein and gene expression were evaluated by immunofluorescence or immunocytochemistry and qRT-PCR, respectively. Cell migration capacity was also evaluated. For CF41.Mg and MDA-MB-468 cell lines, there was an increase in E-cadherin and a decrease in N-cadherin and PARP-1 protein and gene expression after treatment with carboplatin, losartan, both in combination and after AGTR-1 gene edition. There was a decrease in VEGF and PARP-1 protein and gene expression after AGTR-1 gene edition. Moreover, in both lines, reduction in invasion rate was observed after all treatments. Our data suggest that losartan and the gene edition of AGTR-1 by CRISPR/Cas9 were able to block the DNA repair and control the EMT process, such as carboplatin. The results in the canine species are unprecedented, as there are no data in the literature that demonstrate the action of losartan in this tumor type.
Keywords: AGTR-1; Gene edition; Losartan; Mammary tumors; Triple negative cell lines